The effectiveness of Sulh on matrimonial asset division after death of spouse - Sahari, Noorul Huda; Mohd Zin, Najibah; Ibrahim, Norliah; Saidon, Rafeah (Universiti Putra Malaysia Press, 2015)
Distribution of matrimonial asset to deceased’s spouse often faced with obstacles and took longer time to be settled. This is due to the current provision relating to division of matrimonial asset emphasized on the parties’ contribution to determine the appropriate proportion to the deceased’s spouse. Lack of evidence especially in proving the contribution of parties has caused difficulties for courts to reach decision. This study is aimed to examine the effectiveness of sulh with regards the distribution of matrimonial asset upon the death of spouse. The study uses qualitative method by collecting information from unreported cases within the period of 2000-2012 from six zones representing Syariah Courts in Malaysia. Analysis is made based on several variables such as types of matrimonial property, factors for consideration and proportion of distribution of the assets. The findings show that sulh was an effective method to resolve issues relating to the contribution of parties in division of matrimonial asset due to death of spouse. The findings also discovered that exclusive ownership of matrimonial asset especially matrimonial home to the deceased’s wife could provide adequate security and protection for her survival after the death of husband. Therefore, this study suggests that the use of sulh as a mode of dividing the matrimonial asset is to be widely practiced when dealing with the division of matrimonial assets to prevent a costly and lengthy litigation process. Perhaps this is the first study to focus on sulh methods involving distribution of matrimonial asset to spouses after the death of their husband or wife.